PHYTOCHEMICAL SCREENING AND EVALUATION OF ANTISCHIZOPHRENIC ACTIVITY OF METHANOL LEAF EXTRACT OF Hymenocardia acida Tul. (Phyllantaceae) - Danladi, Suleiman; Lawal, Nafisah Bisallah; Alhassan, Aisha Muhammad (FUDMA Journal of Sciences, 2024)
Schizophrenia is a severe brain disorder marked by distortions in cognition, emotion, language, perception, and thought, affects an estimated 20 million individuals globally. In Nigeria, where a significant population relies on herbal medicines, including those derived from Hymenocardia acida, to address mental health needs, there have been traditional claims regarding the plant’s efficacy in treating schizophrenia. This study aims to screen phytochemical constituents and establish the anti-schizophrenic potential of the methanol leaf extract of H. acida. Phytochemical screening revealed the presence of flavonoids, tannins, terpenoids, and steroids in the methanol leaf extract. The Lorke method determined the intraperitoneal median lethal dose (LD50) of the extract to be above 5000 mg/kg in mice. The anti-schizophrenic activity was assessed through various tests, including apomorphine-induced stereotypic behavior, swim-induced grooming, and haloperidol-induced catalepsy. Results indicated that the methanol leaf extract, at doses of 250, 500, and 1000 mg/kg, did not significantly reduce apomorphine-induced stereotypic behavior. However, it exhibited a significant and dose-dependent reduction in the average number of grooming episodes and the duration of swim-induced grooming behavior across all tested doses. Notably, the highest dose (1000 mg/kg) significantly reduced cataleptic effects at 60 minutes post haloperidol administration compared to the negative control. These findings suggest the potential anti-schizophrenic activity of the methanol leaf extract of H. acida, supporting its traditional use in addressing psychiatric disorders.